System-Level Quality Improvement Initiatives for Tobacco Use in a Safety-Net Health System During the COVID-19 Pandemic - Kara Chung; Henry Rafferty; Leslie W. Suen; Maya Vijayaraghavan (SAGE Publishing, 2022)
Introduction: The shift from in-person care to telemedicine made it challenging to provide guideline-recommended tobacco cessation care during the COVID-19 pandemic. We described quality improvement (QI) initiatives for tobacco cessation during the COVID-19 pandemic, focusing on African American/Black patients with high smoking rates. Methods: The QI initiatives took place in the San Francisco Health Network, a network of 13 safety-net clinics in San Francisco, California between February 2020 and February 2022. We conducted direct patient outreach by telephone and increased staff capacity to increase cessation care delivery. We examined trends in tobacco screening, provider counseling, and best practice for cessation care (ie, the proportion of patients receiving at least 1 smoking cessation service during a clinical encounter). Results: In-person visits at the onset of the pandemic was 20% in April 2020 and increased to 67% by February 2022. During this time, tobacco screening increased from 29% to 74%. From March 2020 to March 2021, 34% more patients received provider counseling by telephone than in-person. The trend reversed from April 2021 to February 2022, where 23% more patients received counseling in-person than by telehealth. Best practice care increased by 23% from June 2020 to February 2022: 24% for African American/Black patients and 23% for other patients. Conclusions: Telehealth adaptations to the EHR, targeted outreach to patients, and a multi-disciplinary medical team may be associated with increases in cessation care delivery during the COVID-19 pandemic.